2015
DOI: 10.4236/tel.2015.56088
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Examination of Efficiency Theory of Mergers in Emerging Market India

Abstract: The "inconclusive" existing literature on long-term horizon studies of mergers is the motivation of this paper to reexamine the post-merger performance and explore the reasons of unsatisfactory performance. We test efficiency theory of mergers by examining the industry adjusted operating performance of mergers. Unlike the existing literature which examines the operating performance of mergers at end level (ROA or ROE), we not only examine the operating performance at end level but also analyze the performance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 30 publications
(32 reference statements)
0
7
0
Order By: Relevance
“…The results of the study are also supported by Weston et al (2011) who suggested that M&A ideas could be categorized as value-enhancing activities with motives that include: strengthening market strength; gaining efficiency; gain synergy; reducing transaction costs; and disciplinary action. The main objective of M&A in the banking sector is to achieve co-operation (financial co-operation) in the form of cost reduction or revenue growth but previous research shows a consistent result (Wadhwa and Syamala, 2015;Weitzel and McCarthy, 2011;Daniya et al, 2016).…”
Section: Discussionmentioning
confidence: 96%
“…The results of the study are also supported by Weston et al (2011) who suggested that M&A ideas could be categorized as value-enhancing activities with motives that include: strengthening market strength; gaining efficiency; gain synergy; reducing transaction costs; and disciplinary action. The main objective of M&A in the banking sector is to achieve co-operation (financial co-operation) in the form of cost reduction or revenue growth but previous research shows a consistent result (Wadhwa and Syamala, 2015;Weitzel and McCarthy, 2011;Daniya et al, 2016).…”
Section: Discussionmentioning
confidence: 96%
“…This theory states that mergers only occurs when they are expected to generate enough realizable synergies to make the deal beneficial to both parties; it is the symmetric expectations of gains which results in a friendly merger being proposed and accepted (Jain & Raorane, 2011). If the gain in value to the target is not positive it is suggested that the target firms owners would not sell or submit to the acquisition and if the gains are negative to the bidders owners, the bidder would not complete the deal (Wadhwa & Syamala, 2015). Efficiency theory predicts value creation with positive returns both to the acquirer and the target.…”
Section: Efficiency Theorymentioning
confidence: 99%
“…Organizations will only engages in the merger process if they can correctly and clearly see an efficient utilization of the existing resources and the potentially new set of resources that comes with the mergers. The theory suggests that the main aim behind mergers is to achieve synergies such as the operating and financial synergies that would make it easier to reduce costs, increase the revenues and help the entities achieve other market related objectives (Wadhwa & Syamala, 2015). With such a move, the merger is seen as a prudent use of the organizational resources to help it acquire more resource and be accorded new opportunities that would increase the organization's performance.…”
Section: Literature Review Theoretical Literature Reviewmentioning
confidence: 99%